Ectopic thyroid tissue within thyroglossal duct cyst as the only functioning thyroid tissue and it’s management considerations - Sigdel, Brihaspati; Koirala, Sanjaya; Adhikari, Apar; Ghimire, Ashish; Dahal, Aditya; Shah, Basanta (Journal of Gandaki Medical College-Nepal, 2026)
Functional ectopic thyroid tissue may rarely be present within the walls of a thyroglossal duct cyst, and these may be the only functional thyroid tissue. We described one such case of ectopic thyroid within the thyroglossal duct cyst and its surgical management. A 12-year-old girl presented to us with a gradually increasing, painless midline neck mass that moved with swallowing and tongue protrusion. Ultrasonography showed a well-defined spongiform midline lesion measuring 3.2*1.4 cm in the upper neck. The thyroid scan showed focal increased tracer uptake in the midline upper neck corresponding to the clinically palpable swelling. A Sistrunk procedure was carried out, and the patient was started on thyroid hormone replacement.